2014
DOI: 10.22495/cocv11i4c2p1
|View full text |Cite
|
Sign up to set email alerts
|

Review of corporate governance bundle

Abstract: Due to the importance of corporate governance in our business world today, especially after the frequent non-stop financial crises, and since one corporate governance mechanism may not fulfill the purpose, researchers recently came up with a bundle of corporate governance mechanisms which may complement each other or substitute one another. This paper reviews the literature as regards the evolution, development, current application, and potential future use of this bundle, together with relevant critiques

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
1
0
5
Order By: Relevance
“…Staikouras et al (2007) have examined the South Eastern European (SEE) banking industry over the period 1998-2003 and reveal a positive and significant relationship. Ahmed Mohsen Al-Baidhani (2015) in his study on Islamic banks, in Yemen, along with six GCC countries, has revealed a positive and significant impact of age on ROE confirming the learning curve principle, which suggests that banks become proficient from their past experiences. Higher ROE of older banks may be the result of bank age and the market share, as well as the longer custom and good reputation enjoyed during the course of time.…”
Section: Bank-specific Determinantsmentioning
confidence: 85%
“…Staikouras et al (2007) have examined the South Eastern European (SEE) banking industry over the period 1998-2003 and reveal a positive and significant relationship. Ahmed Mohsen Al-Baidhani (2015) in his study on Islamic banks, in Yemen, along with six GCC countries, has revealed a positive and significant impact of age on ROE confirming the learning curve principle, which suggests that banks become proficient from their past experiences. Higher ROE of older banks may be the result of bank age and the market share, as well as the longer custom and good reputation enjoyed during the course of time.…”
Section: Bank-specific Determinantsmentioning
confidence: 85%
“…Sendo que elementos como separação de propriedade e controle (Brickley & Zimmerman, 2010;Claessens & Yuroglu, 2013;Daily et al, 2003;Denis, 2001;Larcker et al, 2007;Short, Keasey, Wright, Hull, & Nakajima, 1999) e problema de agência (Agrawal & Knoeber, 1996;Beiner, Drobetz, Schmid, & Zimmermann, 2006;Brickley & Zimmerman, 2010;Filatotchev & Allcock, 2010, Hart, 1995Ho, 2005;Mayer, 1998), são inerentes quando a definição tem o viés da Teoria da Agência, baseada em accountability para o acionista, no intuito de melhorar o desempenho. À medida que características como direitos e responsabilidades, estrutura da corporação e envolvimento de outros stakeholders (Aguilera & Jackson, 2010;Al-Baidhani, 2014;Beasley, 1996;Brickley & Zimmerman, 2010;Christopher, 2011;Davis, 2005;Filatotchev & Allcock, 2010;Filatotchev & Boyd, 2009;Gillan, 2006;Hart, 1995;Ho, 2005;Huse, 2005;Larcker et al, 2007;L'Huillier, 2014), são provenientes de outras perspectivas teóricas. Da mesma forma, ao se analisar GC como função de interação entre stakeholders e função stewardship (Agrawal & Knoeber, 1996;Aguilera, et al, 2015;Aguilera & Jackson, 2010;Ahrens et al, 2011;Al-Baidhani, 2014;Beasley, 1996;Beiner, et al, 2006;Brickley & Zimmerman, 2010;Claessens & Yurtoglu, 2013;…”
Section: Governança Corporativaunclassified
“…À medida que características como direitos e responsabilidades, estrutura da corporação e envolvimento de outros stakeholders (Aguilera & Jackson, 2010;Al-Baidhani, 2014;Beasley, 1996;Brickley & Zimmerman, 2010;Christopher, 2011;Davis, 2005;Filatotchev & Allcock, 2010;Filatotchev & Boyd, 2009;Gillan, 2006;Hart, 1995;Ho, 2005;Huse, 2005;Larcker et al, 2007;L'Huillier, 2014), são provenientes de outras perspectivas teóricas. Da mesma forma, ao se analisar GC como função de interação entre stakeholders e função stewardship (Agrawal & Knoeber, 1996;Aguilera, et al, 2015;Aguilera & Jackson, 2010;Ahrens et al, 2011;Al-Baidhani, 2014;Beasley, 1996;Beiner, et al, 2006;Brickley & Zimmerman, 2010;Claessens & Yurtoglu, 2013;Daily et al, 2003;Davis, 2005;Denis, 2001;Ho, 2005;Filatotchev & Allcock, 2010;Filatotchev & Boyd, 2009;Filatotchev & Nakajima, 2010;Gaur, Bathula, & Singh, 2015;L'Huillier, 2014;Mayer, 1998;Tsipouri & Xanthakis, 2004;Turnbull, 1997;).…”
Section: Governança Corporativaunclassified
See 2 more Smart Citations